Comprehensive quali-quantitative profiling of neutral and sialylated O-glycome by mass spectrometry based on oligosaccharide metabolic engineering and isotopic labeling. Issue 28 (20th May 2019) - Nan, Lijing; Li, Jiao; Jin, Wanjun; Wei, Ming; Tang, Mengjun; Wang, Chengjian; Gong, Guiping; Huang, Linjuan; Zhang, Ying; Wang, Zhongfu
Abstract : An isotopic precursor based metabolic amplification and labeling (IPMAL) strategy using the Ac3 GalNAc-α-Bn precursor to simultaneously quantify neutral and sialylated O -glycans. Abstract : Mass spectrometry (MS) analysis combined with stable isotopic labeling is of great importance for quantitatively profiling abnormal sialylated O -glycans associated with disease development, but technically hindered by the poor releasing efficiency of O -glycans from glycoprotein or the labile nature of sialic acid residues at glycans. Herein, we developed an isotopic precursor based metabolic amplification and labeling (IPMAL) technique for relative quantitative profiling of the repertoire O -glycans between normal and tumor cells by ESI-MS. Two groups of cells were incubated with peracetylated benzyl-α- N -acetylgalactosamine (Ac3 GalNAc-α-Bn d0 ) or a heavy labeled peracetylated benzyl-α- N -acetylgalactosamine (Ac3 GalNAc-α-Bn d5 ) precursor respectively to amplify the repertoire of O -glycans as Bn d0/d5 - O -glycans which could achieve the quantitative O -glycome analysis by ESI-MS after derivatization. The established method demonstrates desirable feasibility, accuracy (relative error (RE) ≤ 4.20%), reproducibility (coefficient of variation (CV) ≤ 7.61%, n = 3) and good quantitation linearity ( R 2 > 0.99, n = 3) for five Bn- O -glycans with 2 orders of magnitude. Finally, the method has been successfully applied to quantitative analysis of the repertoire O -glycome changes between normal human liver cell line L02 and human hepatoma cell line SMMC-7721. Moreover, the α-2, 3/2, 6 sialic acid isomers of Bn- O -glycans from these two cells have been further quantitatively distinguished when involved a sialic acid specific derivatization procedure.